NALAR AYAT DAN HADITS TENTANG THALAQ DAN PROBLEMATIKA DENGAN THALAQ DI HADAPAN HAKIM - Shabri, Abdurrahman (El-Sirry: Jurnal Hukum Islam dan Sosial, 2023)
The requirement for a reason for divorce as applied in Indonesia is in accordance with the contents of Surah al-Nisa' (4): 34-35 by using the letter wawu ataf in dalalat al-tartib (showing sequentially), not li mutlaq al-jam'i or li al-mai'yah (together). Therefore, a husband should not immediately say the words talaq to his wife, for example saying "anti-taaliq", but there must be stages that go through and the reasons underlying the talaq. The provisions of the law which require witnesses to pronounce the divorce vow are in accordance with the amar rule in the pronunciation of wa ashidu dhaway adlin by placing the main rule of amar (command) in obligatory and using marji' (reverse place) not the aw fariquhun pronunciation, but returning the fa pronunciation thalliquuhun. In the case of waw ataf it is equated with the rule of condition; so that the terms/ataf apply again to the entire amount, not just to the last amount (sentence).